2019
DOI: 10.1186/s42490-019-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Battling adhesions: from understanding to prevention

Abstract: Adhesions represent a major burden in clinical practice, particularly following abdominal, intrauterine, pericardial and tendon surgical procedures. Adhesions are initiated by a disruption in the epithelial or mesothelial layer of tissue, which leads to fibrin adhesion sites due to the downregulation of fibrinolytic activity and an increase in fibrin deposition. Hence, the metabolic events involved in tissue healing, coagulation, inflammation, fibrinolysis and angiogenesis play a pivotal role in adhesion forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 123 publications
(186 reference statements)
0
75
0
3
Order By: Relevance
“…Postoperative abdominal adhesion formation is frequent and a burden to both patients and clinicians: for example, patients might suffer from small-bowel obstruction requiring surgical interventions, and clinicians might experience increase of workload [ 12 , 13 , 14 ]. A disruption in the epithelial or mesothelial layer of tissue during surgery initiates a series of processes, such as inflammation, coagulation cascade, and angiogenesis, altogether resulting in adhesions [ 15 , 16 ]. Considering the mechanism underlying adhesions, the use of anti-adhesion barriers makes sense in preventing adhesion formation because it separates the surgical area from surrounding tissues and prevents attachment of fibrin clots [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative abdominal adhesion formation is frequent and a burden to both patients and clinicians: for example, patients might suffer from small-bowel obstruction requiring surgical interventions, and clinicians might experience increase of workload [ 12 , 13 , 14 ]. A disruption in the epithelial or mesothelial layer of tissue during surgery initiates a series of processes, such as inflammation, coagulation cascade, and angiogenesis, altogether resulting in adhesions [ 15 , 16 ]. Considering the mechanism underlying adhesions, the use of anti-adhesion barriers makes sense in preventing adhesion formation because it separates the surgical area from surrounding tissues and prevents attachment of fibrin clots [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A disruption in the epithelial or mesothelial layer of tissue during surgery initiates a series of processes, such as inflammation, coagulation cascade, and angiogenesis, altogether resulting in adhesions [ 15 , 16 ]. Considering the mechanism underlying adhesions, the use of anti-adhesion barriers makes sense in preventing adhesion formation because it separates the surgical area from surrounding tissues and prevents attachment of fibrin clots [ 16 , 17 ]. Moreover, a recent study reported that the use of anti-adhesion barriers in open colorectal surgery was even cost-effective in preventing adhesion-related problems [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Im Vergleich zur Laparotomie, die mit einer Vielzahl von peritonealen Adhäsionen einhergeht, werden laparoskopische Eingriffe mit einer schwächeren Ausprägung an peritonealen Adhäsionen in Verbindung gebracht, da sie eine geringere Zerstörung von Epithel-und Mesothelgewebe verursachen. Doch auch hier ist zu beachten, dass es aufgrund des Pneumoperitoneums durch das insufflierte CO 2 zu einer Austrocknung der peritonealen Schichten und durch die hervorgerufene Hypoxie zur Entstehung von Adhäsionen kommen kann [3].…”
Section: Ursachen Und Folgenunclassified
“…Adhäsionen werden nach folgenden Kriterien eingeteilt. So wird je nach Entstehung der Typ de novo (an Orten ohne vorherige Adhäsionen) oder reformed (erneute Bildung nach vorheriger Adhäsioloyse) unterschieden [3]. Der Ort der auftretenden Adhäsionen, der Schweregrad, die Ausdehnung und die Beschaffenheit werden beschrieben.…”
unclassified
“…Introduction. At the present stage, it is considered that adhesions in the abdominal cavity are a natural protective and adaptive reaction in response to peritoneal damage [1,2,3,4]. However, excessive adhesions are not only a pathological process, but it causes intestinal obstruction in children in 62% cases and leads to disability [5,6].…”
mentioning
confidence: 99%